Atrial fibrillation is associated with mortality and increased admission biomarkers reflecting neurohormonal activation and inflammation in patients with ST-elevation myocardial infarction. (3rd May 2023) - Frydland, M; Moeller, J E; Holmvang, L; Helgestad, O K L; Jensen, L O; Goetze, J P; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Righospitalets Forskningsfond (07IO) Lundbeck Foundation (R186-2015-2132). Background: Neurohormonal activation and inflammation is associated with mortality in STEMI patients. We sought to assess, whether AFIB – a known risk factor in MI – also was associated with increased 1-year mortality as well as neurohormonal activation and inflammation in STEMI patients. Methods: In 1892 consecutive STEMI patients from two danish tertiary heart centers biomarkers reflecting neurohormonal activation (copeptin, pro-atrial natriuretic peptide (proANP), and mid-regional pro-adrenomedullin (MRproADM)) and inflammation (ST2) was measured. Patients were stratified according to known AFIB or new onset AFIB on admission vs no AFIB. Results: In total, 198 (10%, 100 known/98 new onset) patients had AFIB, which was associated with increased 1-year mortality (19% vs. 8.4%, p<0.0001). Patients with AFIB were older (mean (SD) age 70 (13) vs 63 (13) years, p<0.0001), had more comorbidity (e.g. hypertension 61% vs. 43%, p<0.0001; stroke 13% vs 6.4%, p=0.002; heart failure 11% vs 2.3%, p<0.0001), lower left ventricular ejection fraction (LVEF) (mean (SD) 41 (13) vs 45 (13), p<0.0001), were more often comatose after cardiac arrest (12% vs 6%, p=0.001), and in cardiogenic shock (CS) (20% vs 9.1%, p<0.0001). Plasma concentration (median (IQR)) of all four biomarkers were higher in AFIB patients (copeptin 124 (39; 298) vs 66 (21; 170) pmol/L; proANP 1678 (1018; 2439) pmol/L; MRproADM 0.96 (0.76; 1.41) vs 0.70 (0.58; 0.90) nmol/L; ST2 48 (34; 74) vs 39 (29; 55) ng/ml, p<0.0001 for all). When adjusting for age, sex, hypertension, previous stroke, LVEF, CS, and being comatose after cardiac arrest, AFIB remained associated with increased plasma concentration of all four biomarkers (two-fold increase – OR (95% CI): Copeptin 1.21 (1.02-1.23); proANP 2.22 (1.82-2.72); MRproADM 2.01 (1.56-2.60); ST2 1.21 (1.03-1.43)). Conclusion: AFIB in STEMI patients is associated with increased admission biomarkers reflecting neurohormonal activation and inflammation and 1-year mortality.